Society and economy framework and principles - Granovetter, Mark S. (The Belknap Press of Harvard University Press, 2017)
In Society and Economy, Mark Granovetter sees the economy as one of many activities in "society"--A term that refers to everything people do with one another and how this adds up to a recognizable whole. Some economic action can be well understood as people rationally using means towards well-defined ends, but much of it is harder to fit into such a simple framework. Actors follow norms that specify the "right" thing to do, at times with passionate belief, and at others, without conscious thought. They trust others when there is no obvious reason to do so. And they wield power over one another that comes from non-economic sources but has major impact on economic outcomes. The book explores how problem-solving actors assemble solutions from this kaleidoscope of principles, in ways that psychologists and philosophers describe as "pragmatic," drawing on arguments ranging from individual psychology to social networks to long-term historical and political analysis.--